COVID-19: Terapi Penghambat IL-1 dan IL-6 - Hendra H (UMSU, 2021)
Abstract: As of February 2021, there are 102,817,575 cases of COVID-19 globally, causing 2,227,420 deaths, and has been declared as pandemic by WHO. Over time, the management of COVID-19 has evolved, namely the use of Interleukin (IL). Patients with severe COVID-19 experience a hyper-inflammatory response to the virus, called